Islamic Law Accommodation for Social Interaction within Temu Manten Tradition - Mahdaliyah, Mahdaliyah; Assaad, Andi Sukmawati; Nur, Muhammad Tahmid (Al-Ahkam, 2024)
The temu manten tradition has been carried out for generations by the Javanese community and the Javanese community who live in Sukamaju District, North Luwu Regency, South Sulawesi Province, Indonesia. This tradition is the culmination of a series of traditional Javanese wedding events, and it is a symbol of the union of two families. This study aims to determine the procession of the temu manten tradition in Sukamaju District, North Luwu Regency, in terms of social interaction and Islamic law accommodated in the tradition. This study is qualitative research with an empirical sociological approach using participatory observation to study the implementation of the temu manten tradition. The results show that the temu manten tradition in Sukamaju is still carried out with some adjustments, and Islamic law can accommodate this tradition through a broader interpretation and flexible application. Temu manten tradition is also a strong medium of social interaction with the community. There has been an acculturation and value shift of temu manten tradition in Sukamaju District with temu manten tradition in Java. To preserve the temu manten tradition in accordance with the principles of Islamic law and in line with the concept of 'urf, it is necessary to conduct continuous education to the community.